RENCANA PENGEMBANGAN SDN 06 SINDANG DATARAN KEBUPATEN REJANG LEBONG - Aman Roy; Rohiat Rohiat; Manap Somantri (UNIVERSITAS BENGKULU, 2017)
The purpose of this study was to describe the State Primary School Development Plan 06 Sindang Dataran Rejang Lebong. The method used descriptive qualitative research with SWOT analysis. Subjects were 06 State Elementary School District of Sindang Dataran Rejang Lebong. Data collection techniques used were interviews, observation and documentation. The results showed that the State Primary School Development Plan 06 Sindang Dataran can be done well